KRITIK SOSIAL TERHADAP PERANG DALAM LIRIK LAGU B.Y.O.B DAN WAR? KARYA SYSTEM OF A DOWN - Kurniawan, Didik (LANTERN (Journal on English Language, Culture and Literature), 2012)
Lyric is a kind of poetry, an artistic work with extraordinary language, extraordinary meaning and multi-unpredictable interpretation. Lyric as a kind of artistic work is one instrument to criticize a problem in war. System of A Down in “B.Y.O.B.” and “War?” used it to criticize various social problems in a war. The objectives of this thesis are to comprehend the poem, to analyzed condition and situation of the society in Iraq War and Persian Gulf War. The methods used were library research, exponential approach and sociology approach. By applying the method of library research, the writer tried to collect some information and other important documents supporting the process of analysis. The exponential approach used to reveal and to comprehend some intrinsic elements of the poem with the idea inside of the poem. On the other hand, sociology approach used to see the description of the society in Iraq War and Persian Gulf War; the description of its society and its problems in a war. Finally, the writer concludes that System of A Down’s “B.Y.O.B.” and “War?” as critic song to various social problem in Iraq War and Persian Gulf War had given clear information about what had been done by the war to the society. By this poem, System of A Down wanted to share his feeling by criticizing the war.